Desensitization of GABA-activated currents and channels in cultured cortical neurons - Frosch, MP (J Neurosci, 1992)
Application of GABA to rat neocortical neurons maintained in cell culture produced a response that declined over several seconds, even in the continued presence of agonist. The decrement could be attributed to both a redistribution of Cl- and a true decline in GABA-induced membrane conductance, or desensitization. The extent and rate of desensitization were dose dependent in a manner similar to the dose dependence of the GABA-induced current, but were not related to the absolute magnitude of the current or to the charge transfer. Bicuculline slowed desensitization while diazepam enhanced the rate of desensitization, consistent with a localization of desensitization to the agonist-receptor binding site. When measured in the whole-cell recording mode, desensitization was voltage dependent, becoming much slower as the membrane was depolarized. Changes in extracellular or intracellular [Ca2+] did not appear to grossly affect the desensitization process or its voltage dependence. GABA-activated single channels, recorded in the outside-out configuration, also desensitized in the continued presence of agonist. However, desensitization differed from that seen in the same neurons in the whole-cell mode. Desensitization was considerably more rapid and did not show any voltage sensitivity. Moreover, single-channel responses often failed to recover after only a few exposures to agonist. Desensitization of GABA responses may play a role in the regulation of cortical inhibition, especially under conditions of intense excitatory and inhibitory synaptic activation.